Validation of the Chinese version General Causality Orientation Scale‐Clinical Population and causality orientations assessing in major depressions. (27th December 2018) - Lei, Wei; Liu, Kezhi; Li, Nian; Liang, Xuemei; Xiang, Bo; Huang, Chaohua; Zhang, Jin; Zheng, Xiaojiao; Chen, Jing
Abstract: Introduction: This study examined the psychometric properties of the Chinese version General Causality Orientation Scale‐Clinical Population (GCOS‐CP) and assessed the causality orientations in patients with major depression disorders (MDDs). Method: The psychometric properties of the Chinese GCOS‐CP were tested in an adults group (study 1). And then, the Chinese GCOS‐CP was given to individuals with and without MDD (study 2). Results: The Chinese GCOS‐CP provided good reliability and validity. MDD showed lower autonomy but higher impersonal orientations relative to healthy controls. Discussion: The GCOS‐CP is suitable for the assessment of motivation in patients with mental disorders in Chinese setting.